(untitled) (Bioscience Journal, 2020)
This study aimed to characterize the chemical composition of crambe grains produced with plant growth regulators in the 2014 and 2015 harvests and stored for 180 days. During crambe cultivation, two foliar sprayings were carried out with the following treatments: 1) control treatment with distilled water; 2) indole-3-acetic acid 100 mg L-1 (IAA); 3) 3-gibberellic acid P.A. 100 mg L-1 (GA3); 4) Stimulate®. After harvesting, the grains were analyzed initially and after 180 days of uncontrolled storage. We checked water content, lipids in hot extraction (HE), lipids in cold extraction (CE), proteins, acidity and antioxidant activity. The Tukey test was used to compare the averages (p<0.05) and the parameters were grouped using a multivariate clustering technique presented in dendogram. The CE and HE lipid contents were reduced after storage, whereas the protein content and antioxidant activity of the grains were not altered by storage. However, the grains that received IAA application showed an increase in the CE lipid content and their preservation after storage. GA3 application, on the other hand, reduced the protein content. Lipid contents remained constant at the end of storage, and the acidity was reduced due to the application of GA3 and Stimulate® plant growth regulators. The 180-day storage changed crambe quality and regulators can assist in preserving grain quality during storage. The CE and HE lipid content and the grain acidity were good indicators for evaluating effects.